On flexibility of agri-businesses: Are small- or large-scale farms more flexible? - Thomas Glauben; Swetlana Renner; Heinrich Hockmann (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2014)
Enterprise flexibility, against the background of ever-faster changing environs, is deemed to be as a critical prerequisite for staying successful in business. Flexibility may be termed in an economic sense as the capability to adjust production schemes to a new situation without significant additional costs. Newlydeveloped methods for flexibility measurement and a comprehensive dataset were used to determine the scope and determinants of flexibility in Polish farm operations. It appears that flexibility of production technology is interrelated to farm specialization: Mixed enterprises are using more flexible technologies than dairy and granivore farms, which in turn are able to react more flexibly than crop production farms. Findings also indicate that small-scale farms have more flexible production systems than large-scale enterprises. This is true to say of all farm types. Small farms are apparently capable of changing their production schemes at lower additional costs and better adjusting themselves to changed market conditions. This may serve to explain the persistence of small-scale or dual agricultural structures in several transition countries, such as Poland. – – Flexibilität von Unternehmen wird vor dem Hintergrund einer sich immer schneller wandelnden Umwelt als eine wichtige Voraussetzung für ein erfolgreiches Bestehen am Markt betrachtet. Flexibilität kann im ökonomischen Sinne als Fähigkeit Produktionspläne ohne erhebliche Zusatzkosten an eine neue Situation anzupassen bezeichnet werden. Anhand neu entwickelter Methoden der Flexibilitätsmessung und eines umfangreichen Datensatzes wurden Ausmaß und Bestimmungsfaktoren der Flexibilität von polnischen Landwirtschaftsbetrieben ermittelt. Es zeigt sich, dass die Flexibilität der Produktionstechnologie mit der Betriebsausrichtung zusammenhängt: Gemischtbetriebe nutzen flexiblere Technologien als Milchvieh- und Veredlungsbetriebe, die wiederum flexibler reagieren können als Pflanzenbaubetriebe. Ferner zeigt sich, dass kleine Betriebe über flexiblere Produktionssysteme verfügen als große Betriebe. Dies gilt für alle Betriebstypen. Kleine Betriebe können offensichtlich ihre Produktionspläne zu geringeren Zusatzkosten umstellen und sich besser an veränderte Marktbedingungen anpassen. Dies mag zur Erklärung der Persistenz kleinbetrieblicher oder auch dualer Agrarstrukturen in einigen Transformationsländern, wie auch in Polen, beitragen.
urn:nbn:de:gbv:3:2-54868
Keywords: 330